DEVELOPMENT OF MATHEMATICS LEARNING DEVISES ON DISCOVERY LEARNING MODEL ON SQUARE AND TRIANGLE MATERIAL FOR THE SEVENTH GRADE STUDENT OF JUNIOR HIGH SCHOOL - Meiana Faniyanti; Syofni; Sakur (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2021)
This research is motivated by the limited mathematics learning tools that are in accordance with the 2013 curriculum. The aim of this research is to produce learning tools in the form of a syllabus, lesson plans (RPP), and student activity sheets (LAS) using discovery learning models in the material of class VII quarters and triangles. SMP / MTs. The development model used in this study is the 4-D model which consists of four stages of development, namely defining, designing, developing, and distributing. Data collection using practical instruments. The learning tools that have been developed are validated by three expert validators. The findings of the study revealed that the results of the syllabus validation analysis were 3.79 or very valid categories, RPP were 3,87 or very valid categories and LAS were 3.82 or very valid categories. The results of this validation analysis indicate that the syllabus, lesson plans, and LAS are considered valid. Furthermore, the results of the practicality trial in the small group for LAS were 3.50 or very practical category. The conclusion of this study is that the mathematics learning tools developed using the discovery learning model in the material of Quadrilateral and Triangles of class VII SMP / MTs which include syllabus, lesson plans and LAS are valid and feasible to use.